The Effect of LEGO Play Therapy on Reducing Anxiety of Hospitalized Preeschool Children - Tangahu, Rahmiyanti; Mohamad, Rini Wahyuni; Yusuf, Zuhriana (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Anxiety in children during hospitalization presents a significant barrier to effective care. When hospitalized, children often exhibit a range of distress behaviors such as aggression, crying, biting, and kicking. Children are individuals with unique thought patterns and environmental understandings. The familiar routines and parental presence at home are absent in the hospital setting, which poses a stark contrast especially for preschool-aged children. This study aimed to assess the impact of LEGO play therapy on reducing anxiety in preschool children hospitalized I the pediatric ward of RSUD Toto Kabila. This quantitative research employed a quasi-experimental design with a one-group pre-post test approach involving a single group of respondents receiving LEGO play therapy. The study included 33 respondents selected through accidental sampling, utilizing questionnaires as the research instrument. Statistical analysis was cocducted using the non-parametric Wilcoxon test. The findings revealed (p-value <0.05) 0.000, meaning LEGO play therapy reduces anxiety in preschool children during hospitalization, with LEGO play therapy as a non-pharmacological intervention to alleviate anxiety in hospitalized children. It is recommended that nursing practioners incorporate this therapy into pediatric care to help reduce anxiety associated with hospitalization.